2002
DOI: 10.1128/jvi.76.4.1697-1706.2002
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 (HIV-1)Quasispecies at the Sites ofMycobacterium tuberculosisInfectionContribute to Systemic HIV-1 Heterogeneity

Abstract: We have recently reported an increased heterogeneity in the human immunodeficiency virus type 1 (HIV-1) envelope gene (env) in HIV-1-infected patients with pulmonary tuberculosis (TB) compared to patients with HIV-1 alone. This increase may be a result of dissemination of lung-derived HIV-1 isolates from sites of Mycobacterium tuberculosis infection and/or the systemic activation of the immune system in response to TB. To distinguish between these two mechanisms, blood and pleural fluid samples were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 57 publications
5
74
1
Order By: Relevance
“…Our findings parallel those of Collins et al 15 that demonstrated divergent HIV evolution in pleural TB granulomas. In both instances, physical separation appears to promote viral Coreceptor usage is indicated as percentage number of sequences.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our findings parallel those of Collins et al 15 that demonstrated divergent HIV evolution in pleural TB granulomas. In both instances, physical separation appears to promote viral Coreceptor usage is indicated as percentage number of sequences.…”
Section: Discussionsupporting
confidence: 70%
“…[10][11][12][13][14] Whether the same is true within TB coinfected granulomas is currently unclear and inconclusive. [15][16][17] Understanding the dynamics of viral evolution within this unique highly compartmentalized but immunologically active environment is important to virus eradication strategies. The nature of the viral variants, their response to treatment, and the mechanisms that govern their progression to sequestration may play critical roles in clinical patient management.…”
Section: Introductionmentioning
confidence: 99%
“…We also found a putative SI phenotype in one of the three macrophage-derived HIV-1 viruses in the BAL fluid (5). The biological phenotype and coreceptor usage of HIV in the alveolar space seem to be different from those in the pleural space, where the nonsyncytium-inducing CCR5-tropic phenotype predominates (12,52,53). Taken together these data suggest that virus derived from AM during TB has an X4 phenotype.…”
Section: Discussionmentioning
confidence: 51%
“…In the CNS, syncytium-inducing (SI) X4 virus can replicate in macrophages (11). In TB, X4 virus is obtained from the lung, whereas R5 virus is found in the pleural space, suggesting compartment-specific support replication of X4 or R5 virus (5,12).…”
Section: P Atients With Coinfection Of Hiv and Pulmonary Tuberculosismentioning
confidence: 99%
“…Since CD4 T cells and macrophages are major components of the granuloma and most of these T cells are likely to be activated, granulomas seem to be an ideal site for HIV replication. Also proinflammatory cytokines induced by TB-host contact seem to favor HIV replication within granulomas (10).…”
Section: Tb-hiv Co-infection Immunology: How Hiv Inhibit Tb Progressionmentioning
confidence: 99%